2010
DOI: 10.1097/mcg.0b013e3181a9ef53
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation of Peripheral Leukocyte Genes in Patients With Active Crohn's Disease and Crohn's Disease in Remission

Abstract: The genes differentially regulated in peripheral leukocytes represent potential new biomarkers for assessing the activity of Crohn's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…53,54 Among patients with IBD, gene expression profiles obtained from whole blood have been utilized to differentiate active from inactive CD. 55 Additionally, gene expression profiles have demonstrated the ability to differentiate between CD, UC, and other non-inflammatory diarrheal conditions. 56 More recently, the Affymetrix GeneChip technology was utilized to generate genome-wide expression profiles to predict disease activity in patients with UC and CD.…”
Section: New Approaches To Biomarkersmentioning
confidence: 99%
“…53,54 Among patients with IBD, gene expression profiles obtained from whole blood have been utilized to differentiate active from inactive CD. 55 Additionally, gene expression profiles have demonstrated the ability to differentiate between CD, UC, and other non-inflammatory diarrheal conditions. 56 More recently, the Affymetrix GeneChip technology was utilized to generate genome-wide expression profiles to predict disease activity in patients with UC and CD.…”
Section: New Approaches To Biomarkersmentioning
confidence: 99%
“…Gene expression profiling in blood is a valuable method for identifying patterns of gene expression related to specific pathologic entities. A series of studies has shown that RNA expression profiles generated from circulating blood can be used to identify patients with a number of conditions, including lung cancer,1 bladder cancer,2 osteoarthritis,3 schizophrenia and bipolar disorder,4, 5 kidney diseases,6, 7 cardiovascular diseases,8–10 Crohn's disease (CD),11 and diabetes 12. Recently, gene expression profiling in blood has also been shown to have utility in distinguishing patients with or without colon cancer 13…”
mentioning
confidence: 99%
“…In several studies we have shown that gene signatures obtained using blood mRNA can identify a variety of conditions occurring in various sites throughout the body, including heart failure [12], inflammatory bowel disease [13,14], psychiatric disorders [15-17] and various cancers [10,18-20]. These studies suggest that blood cells may act as “sentinels” that can mirror health or disease anywhere in the body.…”
Section: Discussionmentioning
confidence: 99%